1999
DOI: 10.1038/sj.bjc.6690705
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid stimulates meningioma cell adhesion to the extracellular matrix and inhibits invasion

Abstract: Meningiomas are tumours derived from the arachnoid and pia mater. During embryogenesis, these membranes develop from the migrating craniofacial neural crest. We have previously demonstrated that meningiomas have characteristic features of embryonic meninges. Craniofacial neural crest derivatives are affected during normal development and migration by retinoic acid. We speculated, therefore, that meningioma cell migration and invasion would be affected in a similar way. In this study we investigated the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Although inactive as an inhibitor of SCLC cell proliferation, RA abrogated the invasive potential of these cell lines however. In line with these observations, it has been reported that RA inhibits the invasive potential of human meningiomas and melanoma cell lines without modifying their proliferation rate (23,27,43). Besides inhibiting invasion, RA increased the expression of trkA and p75 NGF receptors in NCI-N-592 and GLC8 cells and prevented the decrease of NGF receptors occurring during NGF withdrawal.…”
Section: Transcription Of P21supporting
confidence: 63%
“…Although inactive as an inhibitor of SCLC cell proliferation, RA abrogated the invasive potential of these cell lines however. In line with these observations, it has been reported that RA inhibits the invasive potential of human meningiomas and melanoma cell lines without modifying their proliferation rate (23,27,43). Besides inhibiting invasion, RA increased the expression of trkA and p75 NGF receptors in NCI-N-592 and GLC8 cells and prevented the decrease of NGF receptors occurring during NGF withdrawal.…”
Section: Transcription Of P21supporting
confidence: 63%
“…In vitro data suggest that retinoids inhibit tumour invasion. This has been observed in prostate and other carcinomas , Vo et al 1998, Benbow et al 1999, meningioma (Pereda et al 1999) and melanoma (Hendrix et al 1990). One of the explanations may be decreased activity of uPA or tPA or enhanced expression of TIMPs (Hendrix et al 1990.…”
Section: Introductionmentioning
confidence: 93%
“…We also measured the levels of TIMP-1 protein in conditioned media from normal human pituitary and pituitary adenomas by ELISA. For comparison we selected aggressive tumor types known to express high levels of MMPs similar to those produced by pituitary adenomas (28). We found that most of the pituitary adenomas express relatively low or undetectable levels of TIMP-1 compared to aggressive cancer cells (Fig.…”
Section: Mmp Activity In Normal Pituitary and Pituitary Adenomasmentioning
confidence: 99%
“…TIMP-1 was measured by ELISA as previously described (28). Biotrack ELISA systems specific for human TIMP-1 were purchased from Amersham Pharmacia Biotech (Aylesbury, UK).…”
Section: Timp-1 Measurementmentioning
confidence: 99%
See 1 more Smart Citation